THE POSITION OF INSTRUMENTER WITNESS IN MAKING OF NOTARY DEEDS - Agung Iriantoro (NOTARIIL Jurnal Kenotariatan, 2024)
Instrumenter witnesses must be present while notaries are preparing an authentic deed. Therefore, the testimony of instrumenter witnesses can be the primary evidence against Notary deeds that violate legal norms, thus ensuring the safety of the Notary's position. The purpose of this study is to see and make an analysis of the requirements of instrumenter witnesses in the making of Notary deeds and review and analyze the testimony of instrumenter witnesses that can be used as the primary evidence against Notary deeds that violate legal norms. The type of research used in this study was normative legal research, which referred to primary legal materials, secondary legal materials, and tertiary legal materials. The approaches were the statute approach and the conceptual approach. The technique of collecting legal materials was the technique of literature studies. The results showed that the absence of procedures for notary employees was a weakness in providing certainty and information to investigators. The vague legal norms in UUJN were related to the position and requirements of instrumenter witnesses in the making of Notary deeds. The role of instrumenter witnesses did not get legal certainty in the case of a problem regarding the deed made by the Notary. There must be legal protection for instrumenter witnesses who give evidence at trial because the role of the instrumenter with witnesses is generally different. Therefore, the instrumenter witness position in the notary deed involvement is given additionally in the clause in UUJN article 40, which regulates the witness in the making of the deed.